Tinjauan Terapi Empiris Meningitis Nosokomial oleh Enterobacteriaceae Resisten Multidrug - Meli, Ayu; putri, melista (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
Nosocomial meningitis is a hospital-acquired infection of the meninges, frequently occurring after neurosurgical interventions and associated with high mortality. Multidrug-resistant Enterobacteriaceae (MDRE) are a major cause of this infection, presenting challenges in selecting effective empirical antibiotic therapy. This review examines the clinical features, pathogen distribution, and empirical treatment strategies in nosocomial meningitis caused by MDRE, based on a cohort study from two neurosurgical centers in Northern China. Klebsiella pneumoniae was identified as the dominant pathogen, with blaKPC as the most prevalent resistance gene. Mortality risk increased in patients with external ventricular drainage and low Glasgow Coma Scale scores. Most patients received a combination of prophylactic, empirical, and definitive antibiotic therapies. These findings underscore the importance of risk-based treatment strategies and molecular diagnostics to optimize empirical therapy, reduce mortality, and combat antimicrobial resistance in nosocomial meningitis. Keywords: meningitis nosocomial, MDRE, Klebsiella pneumoniae